2020
DOI: 10.22454/fammed.2020.182557
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Subspecialization: A Comparative Analysis of Rural and Urban Clinical Education

Abstract: Background and Objectives: Medical students who train in rural communities are often exposed to physicians practicing a broad scope of care, regardless of discipline. We examined how rural education is associated with practice specialization rates for students who match in primary care or general core specialties. Methods: We linked practice and specialty data (2016 AMA Masterfile dataset), demographics (American Medical College Application Service data), and internal college data for 1974-2011 Michigan State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…17 Recent reports of established programs align with our findings that rurally-trained medical students are more likely to join and sustain the rural, primary care, and family medicine workforce. [17][18][19][20] Compared to UMMS matched peers, RPAP graduates have contributed significantly to the Minnesota rural primary care workforce, primarily as family physicians, supporting the findings of Wendling et al, that choosing family medicine may be the best predictor of enduring impact on the primary care workforce. 17 UMMS supports a rural mission in multiple ways.…”
Section: Discussionsupporting
confidence: 55%
“…17 Recent reports of established programs align with our findings that rurally-trained medical students are more likely to join and sustain the rural, primary care, and family medicine workforce. [17][18][19][20] Compared to UMMS matched peers, RPAP graduates have contributed significantly to the Minnesota rural primary care workforce, primarily as family physicians, supporting the findings of Wendling et al, that choosing family medicine may be the best predictor of enduring impact on the primary care workforce. 17 UMMS supports a rural mission in multiple ways.…”
Section: Discussionsupporting
confidence: 55%
“…The impact of training location can be difficult to isolate because students are generally given a choice about where they want to train, and this regional education is often in the context of an educational pathway program. 10,20,21,[42][43][44][45][46][47] However, Practicing physicians Survey Among graduates in the classes of 1983-1984, underrepresented minority graduates were more likely than white graduates to report that financial aid had influenced their specialty choice. Xu 1996 60…”
Section: Locationmentioning
confidence: 99%
“…Between 2003 and 2013, BS-MD students, who received scholarships that covered full tuition and fees, did not enter primary care specialties at a higher rate than other students. Nguyen 2019 61 most studies of career choice of students training on regional campuses have demonstrated that distributed models lead to higher numbers of primary care physicians, 10,41,[48][49][50] with one exception. 51 In some studies, this association was present even in the absence of a distinct curricular pathway.…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Several urban medical schools have also described success with increasing the number of graduates entering rural practice by opening satellite campuses in rural areas. [8][9][10][11] For campuses or schools located in rural areas, there is a need to identify applicants who will be actively engaged in the communities in which they live, embarking to make positive change. Considering the nation-wide decline in medical student applicants who have a rural upbringing, 12 there BACKGROUND AND OBJECTIVES: Medical schools aim to admit talented learners who are honest, patient centered, and caring, in addition to possessing the required cognitive skills.…”
mentioning
confidence: 99%